Workplace Spirituality and Women Career Advancement among Women Academic Leaders - Kumar, Shubham; Pradeepika, Pradeepika (Universitas Prasetiya Mulya, 2023)
This empirical study aims to delve into the intricate connection existing between workplace spirituality and the advancement of women's careers within the realm of higher education institutions situated in India's National Capital Region (NCR). The study encompasses a comprehensive survey of 177 women faculty members, and its methodology involves the application of standardized scales to gauge workplace spirituality and women's career advancement. The research outcomes highlight a noteworthy and affirmative correlation between workplace spirituality and the advancement of women's careers. In particular, the findings underscore the pivotal role of spirituality as a predictor of career progression for women in the context of higher education institutions. This study not only underscores the significance of nurturing workplace spirituality but also its pivotal role in promoting gender equity and fostering the professional growth of women within the distinct milieu of educational organizations.